To Study Abroad, in Zagreb or in Some Other Croatian City? Social Background, Rationality of Choice and Secondary School Students’ Aspirations Towards the Place of Studying (Croatian Sociological Review, 2020)
The paper examines the aspirations of Croatian secondary school students towards studying abroad, in Zagreb or in some other city in Croatia. The theoretical background of the paper was based on the rational choice theory, typically used in explaining educational decisions in periods of educational transition. A multi-level multinomial regression analysis was conducted using a nationally representative sample of students attending four-year secondary schools (N=10 829). The data were collected during the school year 2017/2018. The results indicate that aspirations towards the place of studying are related to the students’ social background: stronger aspirations towards studying in Zagreb correlate with having at least one parent with higher education and with the active working status of the mother and father, while stronger aspirations towards studying abroad correlate with the higher education of both parents and a higher monthly household income. Students’ aspirations towards studying abroad are also related to the rational choice indicators: greater concern with avoiding downward social mobility, higher estimate of the probability of successful enrolment at and completion of higher education, lower assessment of the value of education in Croatian society and higher assessment of non-compliance with principles of meritocracy in Croatian higher education. On the other hand, aspirations towards studying in Zagreb only correlate with a higher assessment of the social value of education. All effects were independent of the students’ school performance. The findings are interpreted in the context of horizontal inequalities in higher education, pointing to possible implications for the educational policy.